COMPARATIVE STUDY OF FNAC AND CELL BLOCK WITH COMBINED RESULT OF BOTH IN DIAGNOSIS OF BREAST LESIONS - SHUKLA, KHUSHBOO; SIDDIQUE, SWALAHA SADAF; LOKWANI, PRINCE; RAUT, W. K. (International Journal of Current Pharmaceutical Research, 2026)
Objective: Breast lesions, ranging from benign to malignant, are common in clinical practice, cancer in breast being a major health issue in India. FNAC is widely used for diagnosis but has limitations that the cell block technique can address by preserving tissue architecture. This study compares the diagnostic performance of FNAC, cell block, and their combined use. Method: A prospective study involved thirty-two female patients with palpable breast lump. Both cytology smears and cell block preparation has been performed from fine needle aspiration (FNAC) material and compare it with histopathology as the gold standard. Diagnostic metrics were evaluated for each method. Results: FNAC identified most of benign and malignant cases. Cell block provided additional information, improving the ability to differentiate between benign and malignant lesions. The combined approach offered the most comprehensive diagnostic results. FNAC is effective but may struggle with atypical or suspicious lesions. The cell block provides better tissue architecture and clarity, which is particularly useful in difficult cases. The combination of both methods improves the diagnostic process, helping reduce the need for invasive procedures. Conclusion: Combining FNAC with the cell block technique significantly improves the ability to diagnose breast lesions accurately. This approach should be considered for enhanced clinical decision-making and patient management.